2012
DOI: 10.1111/j.1365-3059.2012.02662.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization, phylogenetic comparison and serological relationship of the Imp protein of several ‘Candidatus Phytoplasma aurantifolia’ strains

Abstract: The immunodominant membrane protein Imp of several phytoplasmas within the 'Candidatus Phytoplasma aurantifolia' (16Sr-II) group was investigated. Eighteen isolates from Iran (11), East Asia (5), Africa (1) and Australia (1) clustered into three phylogenetic subgroups (A, B and C) based on the 16S rDNA and imp genes, regardless of geographic origin. The imp gene sequences were variable, with more non-synonymous than synonymous mutations (68 vs 20, respectively), even though many of the non-synonymous ones (75%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…1.1) does not contain a C-terminal transmembrane region or cleavage sites, leading to the assumption that Imp is anchored to the phytoplasma cell membrane by an N-terminal transmembrane region (Berg et al, 1999;Morton et al, 2003). These findings were later supported by analysis of Imp-encoding genes from a number of other phytoplasmas (Kakizawa et al, 2009;Siampour et al, 2013).…”
Section: Predicted Protein Structuresupporting
confidence: 50%
“…1.1) does not contain a C-terminal transmembrane region or cleavage sites, leading to the assumption that Imp is anchored to the phytoplasma cell membrane by an N-terminal transmembrane region (Berg et al, 1999;Morton et al, 2003). These findings were later supported by analysis of Imp-encoding genes from a number of other phytoplasmas (Kakizawa et al, 2009;Siampour et al, 2013).…”
Section: Predicted Protein Structuresupporting
confidence: 50%
“…Nothing is known of the role of "Ca. Phytoplasma asteris" imp in the plant, although this gene is under positive selection in different phytoplasmas (13,15). Imp of "Ca.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also shown that phytoplasma immunodominant membrane proteins interact with vector proteins (10,11) and plant proteins (12) and are subjected to strong positive selection (13)(14)(15). Moreover, phytoplasmas can modulate their genome expression according to the infection stage and the infected host species, as suggested by microarray analysis (16) and gene expression study of pathogen transcription factors (17) and of genes lying within potential mobile units (18).…”
mentioning
confidence: 99%
“…An isolate of LWB phytoplasma maintained in periwinkle (Siampour et al, 2013) was used in this study. Total DNA from LWB-infected and healthy periwinkles was extracted using the cetyltrimethylammonium bromide method (Maixner et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…P. aurantifolia' (16SrII), the causal agent of LWB disease, is restricted to a few genes that do not include SVMs or PMUs. Based on the analysis of conserved genes, including 16S rRNA and the immunodominant membrane protein, LWB phytoplasma was shown to be closely related to 16SrII phytoplasmas (Siampour et al, 2013). In the present study, we obtained sequence information from different regions of the genome of this phytoplasma (including SVM regions) and compared them with their counterparts in PnWB or phytoplasmas of other 16Sr groups for which the genome sequence data are available.…”
Section: Introductionmentioning
confidence: 99%